Online Abuse dan Narasi Hypermasculinity dalam Kasus Perubahan Identitas Gender Aprilio Perkasa Manganang - Muhammad Dicka Ma'arief Alyatalatthaf (Jurnal Wanita dan Keluarga, 2022)
This study aims to determine the forms of Online Abuse and Hypermasculinity narratives that occur in Aprilio Perkasa Manganang’s gender identity change case. Online abuse comments are found on @kumparan and @ manganang92 Instagram account. The Hypermasculinity narrative is also found in the text of the video uploaded by @kumparan and some comments on the two accounts. The Online Abuse Wheel concept of Women's Media Center Speech Project is used to see forms of online abuse. The Hypermasculinity narrative is seen based on traditional masculinity stereotypes through gender roles and sex roles. This research uses Teun A. van Dijk's model of Critical Discourse Analysis methods. The result found that online abuse behavior as a whole, belongs to gender-based bullying category, while the Hypermasculinity narrative in the comments and video text uploaded by @kumparan can polarize the discourse of ‘real men’ and ‘feminine men’.